Internet Freedom and the Impact of Social Media: Political Buzzer Behavior In Indonesia And Thailand - Sihidi, Iradhad Taqwa; Romadhan, Ach. Apriyanto; Salahudin, Salahudin; Widodo, Eko Rizqi Purwo (Magister Ilmu Politik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2025)
The presence of political buzzers in many countries shows that the democratic process has experienced a serious setback. This paper specifically looks at the practice of working political buzzers in Indonesia and Thailand. These two countries were chosen because the condition of their democratic institutionalization is still low, marked by the massive violence, provocations, and black campaigns on social media due to the actions of political buzzers. The internet, which is supposed to strengthen democracy by providing space for egalitarian and democratic political participation through social media, has become a new arena for the practice of violence and the creation of political polarization carried out by political buzzers. To clarify these assumptions, this study uses a qualitative descriptive method. The main data was obtained from literature studies. This study shows that political buzzers in Thailand and Indonesia have the same motivation, namely maintaining the continuity of power. The difference lies in the power relationship, where in Indonesia, buzzers are not directly and legally affiliated with power, while in Thailand, it is the opposite